A Case of New Rapidly Progressing Ground-glass Nodule Lung Adenocarcinoma Near Primary Lesion after Stereotactic Body Radiation Therapy - Wang, Sicong; Li, Linfeng; Cheng, Yuanda (Zhongguo fei ai za zhi, 2024)
Ground-glass nodule (GGN) lung cancer often progresses slowly in clinical and there are few clinical studies on long-term follow-up of patients with operable GGN lung cancer treated with stereotactic body radiation therapy (SBRT). We present a successful case of GGN lung cancer treated with SBRT, but a new GGN was found in the lung adjacent to the SBRT target during follow-up. The nodule progressed rapidly and was confirmed as lung adenocarcinoma by surgical resection. No significant risk factors and related driving genes were found in molecular pathological findings and genetic tests. It deserves further study whether new GGN is related to the SBRT. This case suggests that the follow-up after SBRT should be vigilant against the occurrence of new rapidly progressive lung cancer in the target area and adjacent lung tissue. .